Wealth Accounting, Exhaustible Resources and Social Welfare - Hamilton, Kirk (2012)
The empirical literature on natural resource accounting uses methods which implicitly or explicitly entail measuring changes in total resource asset value when an exhaustible resource is depleted. In contrast, the growth theoretic literature on saving, social welfare and sustainable development is built upon a central finding, that the change in real wealth (as measured by net or 'genuine' saving) is proportional to the change in social welfare. We show that the change in total wealth exceeds the change in real wealth in optimal and non-optimal models of resource-extracting economies. This suggests that the change in social welfare is over-estimated when the change in total resource asset value is used as the measure of depletion. A simple empirical exercise, using World Bank data on 'adjusted net saving', reinforces the results from theory.